Antologia noweli polskiej : lektury szkolne - Wrzosek, Lidia; Golembnik, Malgorzata (Warszawa : Ludowa Spoldzielnia Wydawnicza, "Morex", 1993)
This is an anthology of Polish fiction geared for Junior high and high school students.
Keywords: Short stories, Polish; Polish fiction -- 20th century